THE EFFECTIVENESS OF USING PERKINS AND BLYTHE TEACHING MODEL IN ACQUIRING PHILOSOPHICAL CONCEPTS AMONG ELEVENTH GRADE SECONDARY STUDENTS - Ismael Ibrahim Ahmed (TA'LIM : Jurnal Studi Pendidikan Islam, 2026)
This experimental study investigated the effectiveness of the Perkins and Blythe Teaching for Understanding framework in enhancing philosophical concept acquisition among eleventh-grade students in Kurdistan Region, Iraq. Seventy-two male students from Sêmêl Preparatory School participated in this quasi-experimental design with partial control during the 2024-2025 academic year. The experimental group (n=37) received instruction usFbating the Perkins and Blythe model, while the control group (n=35) followed conventional teaching methods. The study covered three chapters from the Grade 11 Philosophy textbook: Introduction to Philosophy, Logic and Critical Thinking, and Ethics and Moral Philosophy. A 30-item concept acquisition test measuring definition, discrimination, and application levels was administered as pre-test and post-test. Independent samples t-test revealed statistically significant differences (p<0.05) favoring the experimental group in post-test comparison (t=7.528). Paired samples t-test showed significant improvement within the experimental group between pre-test and post-test (t=19.842). The experimental group demonstrated superior performance across all three concept acquisition levels. These findings suggest that the Perkins and Blythe framework promotes deeper understanding of philosophical concepts compared to traditional methods, supporting its integration into philosophy curricula and warranting professional development programs for secondary teachers.